Pengaruh Konservatisma Laporan Keuangan Terhadap Earnings Response Coefficient - DEWI, A.A.A. RATNA (The Indonesian Journal of Accounting Research, 2004)
This research has a purpose to provide empirical evidence about relationship between the financial statements conservatism and discretionary accruals as well as relationship between financial statements conservatism and earnings response coefficient. The hypotheses proposed are: (1) There is a relationship (dependency) between financial statements conservatism and discretionary accruals, (2) There is a relationship (dependency) between earnings response coefficient and financial statements conservatism, especially that earnings response coefficient of the optimist financial statements is larger than earnings response coefficient of conservative financial statements.The conservatism proxy used in this research is accruals obtained from differences between net income and cash flow. The research sample totalled 61 companies which listed and traded in the Jakarta Stock Exchange, selected based on purposive sampling metod. The data used is quarterly data from 1996-2000. The statistical analysis for the first hypothesis is chi-square, and the second hypothesis is t-test.The result shows that: (1) there is a significant relationship between conservatism of financial statements with discretionary accruals (2) the earnings response coefficient of a financial statement which is optimist and persistent differs from that which is conservative and persistent, especially the earnings response coefficient of a statement which is optimist is higher compared to the earnings response coefficient of that tend to be conservative.